The cloud-based learning environment of educational institutions: the current developments - Mariya Pavlivna Shyshkina (Academy of Cognitive and Natural Sciences, 2014)
The purpose of the article is to describe the state of the art of cloud-based learning environment formation and current developments of its design, the main task - analyze of cloud-based learning tools and services use at the educational institutions in Ukraine, the object - the cloud-based learning environment, the subject - the cloud-based learning environment of educational institutions, the main research method is analysis and design. The current tendencies of cloud computing technologies use as the e-learning platform of educational institutions in Ukraine are described. The state of the art of cloud computing services application is revealed. The results of a survey of cloud-based learning tools and services use at the educational institutions in Ukraine are presented. The holistic trends of cloud-based learning environment development are described. The results of holistic learning modeling are reported. Perspective ways of cloud-based learning environment development at the educational institutions in Ukraine are exposed.